Pemanfaatan Limbah Padi (Jerami) Sebagai Bahan Pakan Ikan dan Ternak - Nur Annisa; Wiyoto Wiyoto (Jurnal Pusat Inovasi Masyarakat (PIM), 2019)
Wawasan Tani Cooperative located in Selangor Malaysia has a majority of member are rice farmers. Large land area causing waste rice production of  straw is high, so if we maximilize the utilization it can add some benefit to the coorperative. The purpose of this comunity sevices is to compare suitability the utilization of rice straw for livestock feed and fish feed. The method used through several stages, interview with the head of coorperatuve, observation and searching a cuantitative and cumulative data as a comparation. Result of the data in the form of rice  straw nutrient content, such as protein and energy than compared it with the qualiy requirements of livestrock feed and fish feed. Comparation result proofing that rice straw nutrient still below the quality requirements of livestock feed and fish feed.